Increasing Knowledge of Health Cadres About The Relationship Of Stunting With The Eruption Of The Primery Tooth - Isnanto; Sarwo Edi, Imam; Fitria Ulfah, Siti; Prasetyowati, silvia (Frontiers in Community Service and Empowerment, 2023)
The results of the research by Prasetyowati et al (2019) in the Bugul Kidul Public Health Center, Pasuruan, it was found that as many as 53% of toddlers showed short nutritional status and 47% with very short status. Based on the results of the initial survey, it was found that 90% of parents did not know there was a relationship between stunting and tooth eruption of toddlers. The results of observations of tooth eruption in toddlers with stunting were found to be 77% experiencing slow tooth eruption. One of the duties of cadres is to provide knowledge to the public about health. The community emopowerment program aims to increase the knowledge of cadres in knowing the relationship between stunting and tooth eruption. Increased knowledge of cadres is expected to increase knowledge, attitudes and behavior of the community in preventing stunting and its impact on children's dental health. The method of community service activities is in the form of counseling to candidates. The results of community service activities are that almost 90% of cadres already know the relationship between stunting and tooth eruption. The conclusion that can be formulated is that counseling to cadres in the Bugul Kidul Health Center area of ​​Pasuruan City can increase the knowledge of cadres.